2011
DOI: 10.1007/s12011-010-8939-z
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanum Resulted in Unbalance of Nutrient Elements and Disturbance of Cell Proliferation Cycles in V. faba L. Seedlings

Abstract: Effects of lanthanum (La) on mineral nutrients, cell cycles, and root lengthening have been little reported. The present work investigated these physiological responses in roots of Vicia faba seedlings cultivated in La3+-contained solutions for 15 days. The results showed that the increasing contents of La in the roots and leaves contributed to disbalances of contents of Ca, Fe, Cu, Zn, Mg, Mn, P, and K elements, and potential redistributions of some elements in the roots and leaves. These disbalances might be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 20 publications
1
11
0
3
Order By: Relevance
“…The results of this study revealed that soybean can absorb significant amounts of La from nutrient solution, but only 3% is translocated from roots to shoot. Although few studies have published data on the translocation of La in soybean plants, similar results were reported for vascular plants, which had low concentration of REEs in shoots (Hu et al, 2002;Thomas et al, 2014;Tyler, 2004;Wang et al, 2011). In the present study, there was an increase of 3% in soybean root growth and 8% in shoot growth at low concentrations of La (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…The results of this study revealed that soybean can absorb significant amounts of La from nutrient solution, but only 3% is translocated from roots to shoot. Although few studies have published data on the translocation of La in soybean plants, similar results were reported for vascular plants, which had low concentration of REEs in shoots (Hu et al, 2002;Thomas et al, 2014;Tyler, 2004;Wang et al, 2011). In the present study, there was an increase of 3% in soybean root growth and 8% in shoot growth at low concentrations of La (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…The widespread use of REEs has caused their over-accumulation in soil and water (Wang et al , 2011; Biasioli et al , 2012; Wang et al , 2014). In addition, physiological studies have revealed that REEs have dual effects on plant growth, with low concentrations of REEs improving the growth and yield of crops and high concentrations of REEs having a harmful effect (Wang et al , 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Редкоземельные элементы способны в значительной степени накапливаться корнями растений (Wang et al, 2011a), однако задерживаются поясками Каспари (Nagahashi et al, 1974). Лантан и церий при этом оказывают негативное влияние на рост корня (Diatloff et al, 1995).…”
Section: обсуждение результатовunclassified